Pengangkatan Kanonis Katekis Awam Sebagai Administrator Paroki Sebuah Pendekatan Teologis-Iuridis Canonis - Werang, Basilius Redan (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2006)
The lack of priests in some dioceses in Indonesia has become a constant problem due to the dearth of candidates for the clergy. This situation cannot be overcome if the diocesan Bishop of the mentioned dioceses would con-tinue to entrust parochial ministries only to the ordained ministers. A question then could be raised: Can parochial ministry be entrusted to a lay person? This is a fundamental question because this is not just a case of maximizing the participation of the laity in handling parochial ministries, but also a question about the legality of allowing the laity to handle parochial ministry. Canon 517 § 2 provides the possibi-lity of entrusting the pastoral care of a parish to a person other than priest. For the purpose of this study, I focuse on the person of lay cate-chists due to their specific preparation for such important service. By virtue of law and given by the parti-cular condition of some dioceses in Indonesia as well as their personal capability, some of lay cathecists should be appointed as parochial administrators by the diocesan Bishop given the needs of the people and the place.